Managing environmental knowledge networks to navigate complexity - Jennifer M. Holzer; Tala Awada; Julia Baird; Elena M Bennett; Elizabeth T Borer; Rafael Calderon-Contreras; Peter M Groffman; J. Morgan Grove; Blane Harvey; Gordon M. Hickey; Imogen Hobbs; Murray M. Humphries; et al. (Ecology and Society)
Environmental knowledge networks (EKNs) link research collaborators in a common purpose to produce data and knowledge to better understand social-ecological phenomena and address environmental challenges. Over recent years, as scientists have grappled with how to produce data and actionable knowledge for conservation and sustainability, more EKNs have been established. Although each network is founded for its own purposes and maintains its own goals and ways of operating, these networks are generally managed by scientists to produce knowledge to advance science and decision making. In this Insight article, we articulate key qualities and benefits of EKNs and shows how EKNs can address grand challenges that cannot be answered by a single team or institution, create a diverse, vibrant culture of science and community of practice, and provide innovative solutions and knowledge to society. We also discuss challenges of EKN governance, and how challenges may vary with a network’s development. Finally, based on a synthesis of structured discussions about key issues in EKN management, we share recommendations and best practices, emphasizing management practices that are inclusive, reflexive, adaptive, and flexible, so that others may benefit from our experience leading EKNs.